Peran Mendeley dalam Meningkatkan Kemampuan Menulis Karya Ilmiah Guru-guru di Kabupaten Lombok Barat - Pahrul Irfan; Rifqi Hammad; Kurniadin Abd Latif; Ahmad; Muhammad Zulfikri; Habib Ratu Perwira Negara (Puslitbang Sekawan Institute Nusa Tenggara, 2023)
Publication of scientific work is mandatory for teachers seeking promotion as a requirement to enhance their professionalism. Citing scientific works is crucial in every publication. However, many teachers often encounter difficulties in finding and managing references to be used in research publications. The objective of the Community Engagement Activity is to assist teachers in effectively and efficiently searching for references and organizing the sources to be used as references in their publications. Mendeley, as a reference management application, plays a significant role in improving the ability to write academic papers by providing features that facilitate reference searching and publication writing. The training is conducted through lectures, discussions, and practical exercises. The initial stage involves introducing the Mendeley application and installing it on participants' laptops. Participants are also taught how to collect references in Mendeley for later use in academic writing and how to apply Mendeley in the writing process. The outcome of this engagement is that teachers in West Lombok Regency can effectively master the use of the Mendeley application, thereby supporting their academic writing activities. With these skills, teachers will find it easier to search for references and streamline the process of creating automatic bibliographies